Hypertrophic Cardiomyopathy Mutations of Troponin Reveal Details of Striated Muscle Regulation - Chalovich, J. M.; Zhu, L.; Johnson, D. (Frontiers in Physiology, 2022)
Striated muscle contraction is inhibited by the actin associated proteins tropomyosin, troponin T, troponin I and troponin C. Binding of Ca2+ to troponin C relieves this inhibition by changing contacts among the regulatory components and ultimately repositioning tropomyosin on the actin filament creating a state that is permissive for contraction. Several lines of evidence suggest that there are three possible positions of tropomyosin on actin commonly called Blocked, Closed/Calcium and Open or Myosin states. These states are thought to correlate with different functional states of the contractile system: inactive-Ca2+-free, inactive-Ca2+-bound and active. The inactive-Ca2+-free state is highly occupied at low free Ca2+ levels. However, saturating Ca2+ produces a mixture of inactive and active states making study of the individual states difficult. Disease causing mutations of troponin, as well as phosphomimetic mutations change the stabilities of the states of the regulatory complex thus providing tools for studying individual states. Mutants of troponin are available to stabilize each of three structural states. Particular attention is given to the hypertrophic cardiomyopathy causing mutation, 14 of TnT, that is missing the last 14 C-terminal residues of cardiac troponin T. Removal of the basic residues in this region eliminates the inactive-Ca2+-free state. The major state occupied under these conditions is similar to the inactive-Ca2+-bound state in function and in displacement of TnI from actin-tropomyosin. At saturating Ca2+, those same mutants shift the equilibrium between the inactive-Ca2+-bound and the active state to favor that latter state. These mutants suggest a unique role for the C-terminal region of Troponin T as a brake to limit Ca2+ activation.